Ultra- and hypersonic properties of the critical mixture n - amyl alcohol - nitromethane - ŁABOWSKI, Mikołaj; HORNOWSKI, Tomasz (Archives of Acoustics, 1984)
This paper gives the results of experimental investigations of the propagation velocity and the absorption coefficient of acoustic waves, both in the ultra- and hypersonic ranges, in the critical mixture n - amyl alcohol - nitro-methane for two temperatures. The values of a/f^2 obtained experimentally were compared with those resulting from FIXMAN'S and CHABAN'S theory. It was found that both theories can, with some restrictions, describe experimental results.